Development of Novel Nanocosmeceuticals for Skin Delivery - Ponto, Thellie (Curtin University, 2022)
The search for beauty and eternal youth has been a constant theme throughout human civilisation. These endeavours contribute to the high demand for innovative cosmetic skincare products, with nanotechnology playing an increasingly important role. This doctoral research developed two novel anticellulite and antiaging nanocosmeceutical formulations, that improved the delivery and stability of active ingredients, and skin usability. The research highlighted the importance of implementing a pharmaceutical quality by design approach to formulate high-quality products.